The educational potential of black biographies in basic education from the book Enciclopédia Negra - Aline Sônego; Alícia Quinhones Medeiros; Gabrielle de Souza Oliveira (Tópicos Educacionais)
This article aims to reflect on how much black biographies can operate as an interesting methodology for working individual trajectories of black people and the socio-historical context experienced by them. Black biographies are highlighted as educational potential in the anti-racist struggle, as well as the role of identification and representation that teachers, students and black students can experience through this historiographical tool, which enables the (re)knowledge of artists, intellectuals, professionals, religious and civil authorities, among other forgotten social performances, in the national and regional sphere. The aim is to strengthen the implementation of law 10,639/2003 and Anti-racist Education in curricula at different levels and modalities. At the end is presented the book Enciclopédia negra: biografias afro-brasileiras and space is opened to think about examples of personalities/entities and the potentiality of their employment in the classroom.